Penguatan Kapasitas Anggota Baru KSP Kopdit Sartika Ende melalui Pendidikan Koperasi berbasis Analisis Kehidupan Sosial dan Pengelolaan Keuangan Rumah Tangga: - - Fransiskus Korosando; Manggu Ngguna Raji (LOSARI DIGITAL, 2026)
This community service program aims to improve the understanding and capacity of new members of the KSP Kopdit Sartika Ende through cooperative education based on an analysis of the factual social life of the Ende community and household financial management. The activity was conducted at the Flores Mandiri Cooperative Center (Puskopdit Flores Mandiri) in Paupire Village, Central Ende District, Ende Regency, targeting new members. The implementation method included material delivery, participatory discussions, and simple mentoring related to household financial planning and the responsible use of cooperative services. The activity material, in the form of member education modules, was tailored to the socioeconomic conditions and lifestyle characteristics of the local community. Results of the activity demonstrated an increased understanding of cooperative principles among members, the importance of planned household financial management, and an awareness of the link between social practices and economic obligations as members and the institutional sustainability of KSP Kopdit Sartika Ende. The average participant satisfaction rating was 4.48 (very satisfied). This indicates that this activity provides short-term benefits and has the potential to encourage sustainable changes in economic behavior.